Photocatalytic degradation of 2,4-dichlorophenol using silver halides catalysts - Tichapondwa, Shepherd Masimba (University of Pretoria, 2022)
Dissertation (MEng (Water Utilisation Engineering))--University of Pretoria, 2022.